2017
DOI: 10.5864/d2017-018
|View full text |Cite
|
Sign up to set email alerts
|

Over-confident and under-competent: exploring the importance of food safety education specific to high school students

Abstract: Abstract:The objective of this study was to explore age-specific reasons why food safety education might be important for high school students (in Ontario, Canada), from a variety of expert perspectives. In May 2014, semi-structured key informant interviews (n = 20) were conducted with food safety and youth education experts. A thematic analysis of verbatim transcripts of the interviews was conducted. Participants identified three major reasons why food safety is important for high school students: (i) they ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…Previous research with children, young people and university students across Europe, Australia, Canada and USA suggest a lack of knowledge, concern and perceived susceptibility to foodborne illness [4][5][6][7][8]. While findings report risky behaviours of young Educ.…”
Section: Introductionmentioning
confidence: 67%
“…Previous research with children, young people and university students across Europe, Australia, Canada and USA suggest a lack of knowledge, concern and perceived susceptibility to foodborne illness [4][5][6][7][8]. While findings report risky behaviours of young Educ.…”
Section: Introductionmentioning
confidence: 67%
“…The codebook was then used to code all transcripts (including the 5 used to develop the preliminary codes), and was refined as needed, resulting in a final codebook that contained the most important areas to cover when teaching food safety to high‐school students. Additional details on study methods are reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Behaviour change has been linked to individual's perception of their own risk in behaviour models (Ahmed, Naik, Willoughby, & Edwards, 2012). Young people are an important audience for education on the risk of improper food hygiene and as they tend to be both over-confident in their perception of personal risk and practice more unsafe behaviours (Diplock et al, 2017). By educating children at a young age we can influence future behaviour and habits before they are even formed, setting a solid foundation for healthy behaviours and choices around food.…”
Section: Why Educate and Communicate Risk To Young People?mentioning
confidence: 99%